‘Mother Earth’ is an Ancient Meme in the Global North: Continuity between Eurasian-American ‘Mother Earth’ Concepts Demonstrated in the Athabaskan Case - Wilson, Joseph A P (Journal for the Study of Religion, Nature and Culture, 2024)
In this response to Sam Gill, I contend that European colonizers were not the first to combine and synthesize the goddesses of Eurasia and North America. I suggest that Athabaskan-speaking Native Americans share one identifiable Mother Earth concept with Yeniseian linguistic cousins in post-neolithic Siberia. Further, I regard this concept as congenitally related to a particular Mother Earth deity common to late ancient north Europe, via the multiethnic cultural continuum of the grassland steppe corridor connecting ancient central Europe to Siberia.